2016
DOI: 10.14202/vetworld.2016.342-345
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of induced estrus and conception rate following Ovsynch and Ovsynch based gonadotropin-releasing hormone treatments initiated on day 6 of estrous cycle in repeat breeding crossbred cows

Abstract: Aim:The aim was to evaluate the estrus response, incidence of accessory corpus luteum formation and fertility following different hormonal protocols in repeat breeding crossbred cows.Materials and Methods:This study was carried out on 24 repeat breeding crossbred cows allotted into four groups. Cows of Group I was not given any treatment, Group II was treated with gonadotropin-releasing hormone (GnRH) injection on day 6 post-estrus, Group III was treated with Ovsynch protocol, and Group IV was treated with Ovs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
1
6
1
1
Order By: Relevance
“…Higher estrus induction response (100%) with Ov_synch protocol in acyclic cows as observed in the present study has also been reported by Virmani et al (2013), Buhecha et al (2015) and Ahmed et al (2016). However, relatively lower induction response of 20.0 to 67.0% has been reported by others (Mahour et al, 2012;Naikoo et al 2016).…”
Section: Estrus Induction Response and Induction Intervals In Acyclic/ Anestrus Cowssupporting
confidence: 86%
“…Higher estrus induction response (100%) with Ov_synch protocol in acyclic cows as observed in the present study has also been reported by Virmani et al (2013), Buhecha et al (2015) and Ahmed et al (2016). However, relatively lower induction response of 20.0 to 67.0% has been reported by others (Mahour et al, 2012;Naikoo et al 2016).…”
Section: Estrus Induction Response and Induction Intervals In Acyclic/ Anestrus Cowssupporting
confidence: 86%
“…This research selected cattle traditionally raised in the countryside. The onset of estrus in this study was different from 18.43±0.48 hours in Jersey cows (Bhat and Bhattacharyya, 2012), and 20.07 -21.458 hours in India cattle (Ahmed et al, 2016). The onset of estrus in this study was within the normal range, i.e.…”
Section: Resultscontrasting
confidence: 69%
“…This increase in PR was probably due to the fact that a combination of GnRH and PGF2α in the P4-based fixed-time AI programme results in synchronous follicular wave emergence, timely follicular development, synchronous ovulation following the last injection of GnRH ( Kim et al., 2007 ), and it can overcome the problem of delayed ovulation and anovulation in repeat-breeder dairy cattle ( Bhattacharyya & Hafiz, 2009 ). As stated above, repeat breeder heifers have a smaller preovulatory LH surge than virgin heifers ( Gustafsson et al., 1986 ) and, therefore, an increase in the spontaneous LH surge that results from the treatment of GnRH at onset of the final stage of DF development affects the fertility favourably ( Ahmed et al., 2016 ; Kaim et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%